THE ROLE OF HORMONAL IMBALANCE IN WOMEN'S REPRODUCTIVE HEALTH AND ITS CORRECTION - Rustamova Fotimakhon Umidjon qizi; Rustamova Zukhrakhon Umidjon qizi (Web of Journals Publishing, 2025)
Hormonal imbalance is a major factor in women’s reproductive health, responsible for nearly half of infertility cases. Its causes include endocrine disorders such as polycystic ovary syndrome, thyroid dysfunction, metabolic syndrome, and age-related changes. Disruption of the hypothalamic-pituitary-ovarian axis leads to ovulation disorders and endometrial dysfunction. Clinical signs include menstrual irregularities, infertility, and androgen excess. Diagnosis involves detailed hormonal analysis of follicle-stimulating hormone, luteinizing hormone, prolactin, estrogens, progesterone, and thyroid-stimulating hormone, along with ultrasound examination. Treatment combines hormonal therapy, insulin-sensitizing drugs, lifestyle changes, and innovative personalized approaches based on genetic and metabolic screening.
Keywords: Hormonal imbalance, reproductive health, Polycystic Ovary Syndrome, endocrine disorders, hormone therapy.